2017
DOI: 10.1021/acs.iecr.7b02266
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Supported Ionic Liquid Catalysts Systems—From Idea to Applications

Abstract: The modeling of chemical reactions studied in small scale, often carried out in Academia, is very important since it gives more information about the system and better possibilities to scale-up the processes in the future. Supported ionic liquid catalysts (SILCAs) have been studied in a number of different processes. However, the modeling of these processes have been studied only in a few cases. In this paper the sample cases are reviewed. These processes include hydrogenation of unsaturated aldehydes as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Hence, the development of novel and efficient heterogeneous ionic liquid catalysts are in great demand. Recently, a large number of studies on the immobilization of homogenous ILs on diverse solid support materials have been reported . The inherent advantage of heterogeneous catalysis are the easily recovering and recycling catalysts, allowing low ILs loading in the transformations .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the development of novel and efficient heterogeneous ionic liquid catalysts are in great demand. Recently, a large number of studies on the immobilization of homogenous ILs on diverse solid support materials have been reported . The inherent advantage of heterogeneous catalysis are the easily recovering and recycling catalysts, allowing low ILs loading in the transformations .…”
Section: Methodsmentioning
confidence: 99%
“…25–27 The isomerization of APO and the commercialization of value-added products were achieved by the use of [NB4MPy][BF 4 ] ( N -butyl-4-methylpyridinium tetrafluoroborate) and [ N (3-OH-Pr)Py][NTf 2 ] ( N -(3-hydroxypropyl)pyridinium bis(trifluoromethylsulfonyl)imide) IL supported catalysts with maximum 20 and 21% selectivity of TCV, respectively. 28,29 The previous literature suggested that acidic groups, like –SO 3 H, –PO 3 H, phosphotungstic acid, and –COOH, and metals like Zn, Ag, Fe, Co, and Ti give TCV, whereas Lewis acids like ZnCl 2 , ZnBr 2 , FeCl 3 , and AlCl 3 give CA. 29–34 It is well known in literature, solvents play an important role in isomerization reactions like the polar aprotic solvents DMA (dimethylacetamide) and DMF (dimethylformamide) highly prefer TCV, whereas the non-polar solvent toluene prefers CA.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 The previous literature suggested that acidic groups, like -SO 3 H, -PO 3 H, phosphotungstic acid, and -COOH, and metals like Zn, Ag, Fe, Co, and Ti give TCV, whereas Lewis acids like ZnCl 2 , ZnBr 2 , FeCl 3 , and AlCl 3 give CA. [29][30][31][32][33][34] It is well known in literature, solvents play an important role in isomerization reactions like the polar aprotic solvents DMA (dimethylacetamide) and DMF (dimethylformamide) highly prefer TCV, whereas the non-polar solvent toluene prefers CA. [30][31][32] These solvents are difficult to evaporate because they have high boiling points.…”
Section: Introductionmentioning
confidence: 99%